Экономическая сущность санации и реструктуризации промышленных предприятий - Перерва, Петр Григорьевич; Товажнянский, Вячеслав Леонидович (НТУ "ХПИ", 2015)
В статье проведен анализ предпосылок проявления финансового кризиса на предприятиях машиностроительного комплекса Украины. Проведен анализ объемов производства продукции на предприятиях Харьковской области. Проведено методологическое исследование понятий "кризис", "санация", "реструктуризация". Разработаны методические рекомендации по преодолению симптомов кризиса на промышленных предприятиях.

The article analyzes the prerequisites of manifestation of the financial crisis on the enterprises of machine-building complex of Ukraine. Analysis of production volumes at the enterprises of the Kharkiv region. A methodological study of the concepts of "crisis", "rehabilitation", "restructuring". The methodical recommendations for overcoming the symptoms of the crisis in the industry. Based on studies of the existing methodological support of the diagnosis of the crisis and the threat of state bankruptcy refined classification of methodological approaches with the use of modern methods of diagnostics of bankruptcy and theoretically sound criteria: on the basis of performance indicators (depending on the status of the methods of forming estimates made by research methodology estimated figures from the time of diagnosis, the level of detail of indicators) and on the basis of economic - mathematical and statistical model and methods (depending on use of the balance model, the use of factor analysis, the use of statistical analysis, the use of mathematical tools, techniques of forming general conclusions). The recommendations can be used by industry for anti-crisis monitoring. They are especially important for the machine-building enterprises.
The economic essence of rehabilitation and restructuring of industrial companies
Keywords: финансовый кризис; машиностроительные предприятия; антикризисный мониторинг; объемы продукции; rehabilitation; restructuring; crisis; machine-building; products; manufacturing